Culture of risk prevention at the University Enrique Guzman y Valle–La Cantuta - Calderón-Pacheco, Rosabel (2022)
This article, under a documentary review, analyzes the importance of the implementation of security management tools in a higher education institution, through a sample of twenty-eight (28) teachers, through the administration of evaluation surveys. The research carried out is non-experimental, descriptive-correlational. Conclusion, it is evident that the implementation of safety management tools such as the safety plan, hazard identification, risk assessment and control (IPERC), work protocols, among others, allowed improving the teacher's work environment, through knowledge of your risks to which you are exposed in the workplace and the actions to be taken to eliminate or minimize the risk factor. In addition, the awareness of the presence of the teacher in carrying out the development of the plan and program of security of the university. The continuity of periodic evaluations is recommended to measure the evolution of the culture of prevention and to adjust the use and/or implementation of management tools based on the result of the evaluation, generating the establishment of a circular intervention model against the safety and health of teachers.